2020
DOI: 10.3389/fnins.2020.579938
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Night Shifts: Poor Sleep Quality Exacerbates Psychomotor Performance

Abstract: In Europe, 40% of health-care employees are involved in shift work. The altered sleep/wake rhythm of night-shift nurses is also associated with deteriorated cognitive efficiency. In this study, we examine the effects of the night shift on psychomotor performance, sleepiness, and tiredness in a large sample of shift-working nurses and evaluated if poor sleep quality, sex, age, or years on the job could impact on a better adaptation to shift work. Eighty-six nurses with 8-h-rapidly-rotating-shifts were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
2
42
1
1
Order By: Relevance
“…A multiple regression analysis using the enter method was performed to identify the predictors of sleep quality. The standardized residuals satisfied the assumption of normality on the Kolmogorov-Smirnov test and the assumption of equal variance on the Breusch-Pagan test, thereby confirming a good fit of the regression model (Table 4); for the regression model, we selected the predicting variables that were correlated to overall sleep quality (Table 3) and that were indicated to influence sleep quality in previous studies [20,35]. This analysis used chronotypes, SJL, VSH scores, age, and day-shift fatigue as the independent variables and PSQI scores as the dependent variable.…”
Section: Sleep Qualitymentioning
confidence: 54%
See 1 more Smart Citation
“…A multiple regression analysis using the enter method was performed to identify the predictors of sleep quality. The standardized residuals satisfied the assumption of normality on the Kolmogorov-Smirnov test and the assumption of equal variance on the Breusch-Pagan test, thereby confirming a good fit of the regression model (Table 4); for the regression model, we selected the predicting variables that were correlated to overall sleep quality (Table 3) and that were indicated to influence sleep quality in previous studies [20,35]. This analysis used chronotypes, SJL, VSH scores, age, and day-shift fatigue as the independent variables and PSQI scores as the dependent variable.…”
Section: Sleep Qualitymentioning
confidence: 54%
“…Furthermore, sleep quality is poor regardless of nurses' shift schedules [40], highlighting the need to identify and intervene in the factors that affect sleep quality among rotating shift nurses. The sleep quality of nurses working in shift affects the working performance, and the degree of disturbance was significantly higher when sleep quality during the night shift is poor [35]. In the preceding study, nurses complained of difficulty in sleeping during night shifts in particular [14], even though the number of night shifts was the least compared to other shifts, to understand the factors affecting the overall sleep quality of shift workers, we should find the influence of sleep quality during night shift.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced sleep quantity and quality seem to predict greater subjective sleepiness (Geiger-Brown et al, 2012 ). A recent study by Di Muzio et al ( 2020 ) showed the critical role of sleep quality (as assessed by the Pittsburgh Sleep Quality Index, PSQI; Curcio et al, 2013 ) in exacerbating the decline of psychomotor vigilance in a sample of night shift nurses. Also, individual chronotype affects night shift tolerance, although the exact nature of this relationship is still a matter of debate (Saksvik et al, 2011 ).…”
Section: Future Directions In the Management Of Night Shift Nursesmentioning
confidence: 99%
“…Such working arrangements, for example, have been associated with cardiovascular disease (Torquati et al, 2018 ), cancers (Wang et al, 2015 ; Gan et al, 2018 ; Pahwa et al, 2018 ), metabolic disturbances (Watanabe et al, 2018 ; Gao et al, 2020 ), sleep disturbances (Pallesen et al, 2010 ), gastrointestinal disorders (Knutsson and Bøggild, 2010 ), and impaired reproductive health (Stocker et al, 2014 ), as well as impaired mental health (Torquati et al, 2019 ). Furthermore, shift work and night work have also been linked to negative organizational outcomes such as accidents (Fischer et al, 2017 ), impaired cognitive efficiency (Di Muzio et al, 2020 ), sick leave (Merkus et al, 2012 ), low job satisfaction (Jamal, 1981 ), and turnover and turnover intention (Pisarski et al, 2006 ; Flinkman et al, 2008 ). The underlying mechanisms for the negative health consequences are not fully understood but involve most likely circadian disruption leading to neuroendocrine and cardiometabolic stress, curtailed and disturbed sleep causing altered immune functioning and cellular stress, and risk behaviors and psychosocial stress with cognitive impairment and poor emotion regulation as consequences (Kecklund and Axelsson, 2016 ).…”
Section: Introductionmentioning
confidence: 99%